2004
DOI: 10.1121/1.1815091
|View full text |Cite
|
Sign up to set email alerts
|

Perception and annoyance due to wind turbine noise—a dose–response relationship

Abstract: Installed global wind power increased by 26% during 2003, with U.S and Europe accounting for 90% of the cumulative capacity. Little is known about wind turbines' impact on people living in their vicinity. The aims of this study were to evaluate the prevalence of annoyance due to wind turbine noise and to study dose-response relationships. Interrelationships between noise annoyance and sound characteristics, as well as the influence of subjective variables such as attitude and noise sensitivity, were also asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
283
4
8

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 306 publications
(317 citation statements)
references
References 20 publications
11
283
4
8
Order By: Relevance
“…It could be that the increased annoyance of the residents is a consequence of a generally higher noise sensitivity of that group but such tendencies should be counteracted by the PNE procedure unless the pink noise is excepted from the increased noise sensitivity. Moreover, the residents group can not be considered representative for people in general living near turbines as the majority of the population exposed to wind turbine noise are not bothered [1,2].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It could be that the increased annoyance of the residents is a consequence of a generally higher noise sensitivity of that group but such tendencies should be counteracted by the PNE procedure unless the pink noise is excepted from the increased noise sensitivity. Moreover, the residents group can not be considered representative for people in general living near turbines as the majority of the population exposed to wind turbine noise are not bothered [1,2].…”
Section: Discussionmentioning
confidence: 99%
“…However, plants of wind turbine often concern neighbors because of anticipated disturbance of the visual and acoustic environment. Among residents living close to wind turbines, their noise is typically a source of annoyance [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
“…These studies report complaints due to qualities referred to as "swishing", "thumping" or "throbbing" (among others), which often occur at the blade pass frequency (Oerlemans & Schepers 2009, Pedersen et al 2009, Pedersen & Persson Waye 2004, Persson Waye & Öhrström 2002, Van den Berg 2004. Characterisation of these noise qualities is hindered by the subjective and interchangeable use of the terms "throbbing", "swishing" and "thumping" in the literature.…”
Section: Adverse Wind Farm Noise Characteristicsmentioning
confidence: 99%
“…Some people living near low-frequency industrial noise have reported being annoyed by, among other symptoms, feelings of throbbing and rumbling sensations (Pedersen et al 2009;Pedersen & Waye 2004). Such reports may possibly be explained by amplitude modulation of audible sounds by low-frequency noise and infrasound.…”
Section: Introductionmentioning
confidence: 97%